Telecosmos : The Next Great Telecom Revolution - Edwards, John (New Jersey Wiley-Interscience, 2005)
Although telecom companies are battling for survival, technology is moving forward. In research laboratories around the world, powerful new technologies are being developed that will shape tomorrow's communications world. Telecosmos will look at the many different telecom concepts that will be adopted by both consumers and businesses in the years ahead.
Include Glossary, Index and Illustration
Keywords: Telecommunication--Technological innovations -- Electronic apparatus and appliances--Technological innovations